Widespread tissue delivery of antagomiRs via intramuscular administration - Christodoulos Messios; Andrie Koutsoulidou; Leonidas A. Phylactou (Molecular Therapy: Methods & Clinical Development)
Muscles, traditionally recognized for their role in locomotion and breathing, also participate in tissue communication. Extracellular microRNAs (miRNA) have been identified as key players in intercellular and inter-organ communication in muscle and other tissues. We have previously shown that intramuscular administration of an antagomiR led to the repression of target miRNA in neighboring skeletal muscles. This study investigated whether antagomiRs could be delivered to distant muscle and other tissues following intramuscular administration. We designed antagomiRs targeting a muscle-specific miRNA, miR-133b; a ubiquitously expressed miRNA, miR-16; and a scrambled oligonucleotide. Although all sequences were detected in neighboring skeletal muscles and distant tissues following intramuscular administration, antagomiR-133b showed the highest accumulation and efficacy in various tissues. This is the first study to provide evidence that intramuscular administration of antagomiRs could be utilized to achieve efficient and widespread distribution in tissues. This in turn could form the basis for alternative future therapeutic approaches.